Edukasi Pencegahan Bullying sebagai Upaya Promosi Kesehatan Jiwa di MAN 1 Aceh Besar - Nurul Amna; Ellyza Fazlylawati; Khaira Rizki; Sri Jumiati; Amalia Risca; Abqariah Abqariah; Ayu Maitasya; Eva Yusniar; Muhammad Aril; Sri Rahayu; Jumaivira Jumaivira (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
Bullying remains a serious problem in schools today, as evidenced by the number of victims and perpetrators, which continues to rise over time. This can have negative consequences—particularly psychological effects—on victims, and it creates a learning environment that is unsafe, uncomfortable, and not conducive to student learning. This phenomenon indicates that the incidence of bullying among students in Indonesia remains a serious problem. The objective of this activity was to increase students’ knowledge about bullying at MAN 1 Aceh Besar. The results of the activity show that, prior to the educational session, the majority of students did not have an accurate understanding of bullying; however, after the session, their knowledge improved, with 91% now having an accurate understanding of bullying. It can be concluded that there was an increase in knowledge following the educational session. It is hoped that this educational program can be implemented on an ongoing basis to reinforce knowledge and promote anti-bullying behavior within the school environment.